The Effect of Head Turn and Illumination on the Perceived Direction of Gaze. (May 2013) - West, Roger W
Thirty observers judged the direction of monocular and binocular gaze from a model's LCD-imaged head when the head, gaze, and illumination were either straight or turned 20.6° to the side. The judged direction of binocular eye contact from a turned head was judged to go past the direction of the observer, while judged monocular gaze from the eye toward the observer followed that for binocular gaze. Although judged monocular gaze from the eye away from the observer also passed the observer, it did so by a smaller amount. The judged direction of binocular gaze in the same direction as the head turn was judged to pass the direction of the head turn. The judged direction of monocular gaze from the eye away from the observer was nearly true, but the judged direction of monocular gaze from the eye toward the observer was judged as closer to the observer than true. Illumination of the model's head from the side made the direction of both head turn and gaze appear to move away from the direction of the light source. These results are discussed in connection with angle k and the perceived direction of head turn.